THE INFLUENCE OF WORK ETHIC AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Norawati, Suarni; Harahap, Welfinasari (JURNAL ILMIAH EDUNOMIKA, 2024)
Performance is the achievement of an employee's work results within a certain time period based on established standards. Many factors can influence employee performance, but this research only uses the variables work ethic, work discipline and employee job satisfaction. This research aims to determine the direct influence of work ethic and work discipline on employee performance and the indirect influence of work ethic and work discipline on employee performance through job satisfaction; This research uses primary data obtained using a questionnaire. The sample for this research was 86 employees of the Pekanbaru City Public Works and Spatial Planning Department, where the sampling technique was carried out using the census method. The research data analysis using the SEM method, which used the SmartPLS program in data processing, and hypothesis testing. The research findings proved that work ethic was not proven to have a significant effect on employee performance, work discipline has been directly proven to have a significant effect on employee performance, there is an indirect influence of work ethic on employee performance through job satisfaction, there is an indirect influence of work discipline on employee performance through job satisfaction. Keywords: Performance, Work Ethic, Discipline, Satisfaction, Performance